Perlindungan Hukum Atas Hak Asasi Anak Memperoleh Pendidikan - Johan Jasin (JURNAL LEGALITAS, 2009)
Child Presence in a family is not only becomes hungering and hope, but that\'s God\'s Mercy and God\'s trust. As trust, child like adult man, has basic rights like life rights, talks and have a religion. To enjoy this rights betterly, child haw other rights. For example education, that by international world has been poured in universal Declaration of Human Right, convention of children right and document of other regional, as reference and obligation banding member tate PBB.For Indonesian nation, basis latu, arrangement, protection, enforcer of chlid basic rights in education, met in UUD 1945 formulated through UU/39/1999,UU/20/2003 and UU/20/2003. The law and regulation presence indicates that in formal yuridis of chlid basic rights to education has been given protection, but government has not optimal to implementing of their responsibility. The Government with support from all stakeholder must seriously upholds the rule,because success of education will yield quality and excellent human resource that will be builds and positions this country paralel and can vie with other state in global era. Kata Kunci : Perlindungan Hukum, Hak Asasi Anak, Pendidikan.